The endemism in Mexican Liliopsida - Espejo Serna, Adolfo (Instituto de Ecología, A.C., 2012)
An updated cheklist of the Liliopsida endemic to Mexico is presented. Of the 4,542 species of native monocots that inhabit the national territory, 2,010 are strict endemics. The number increases to 2,764 if we consider the Rzedowski´s Megamexico 3 concept. Data about the number of endemic taxa by family, genera and state, and other analysis related to the endemic representation by life forms and some examples of ecological endemism are included.